A Review and Analysis of the Existing Research Streams in Continuous Audit - Brown,Carol; Wong,Jeff; Baldwin,Amelia A. (Journal of Emerging Technologies in Accounting, 2007)
A growing body of literature related to continuous auditing topics has developed. Advances in information technology and web-based applications are making monitoring and control of operations through continuous auditing increasingly important. The objective of this paper is to summarize and provide a framework for classifying the contributions of the diverse literature addressing the topic of continuous audit. This paper was intended to provide researchers and practitioners with a background in continuous audit topics. Our broad view the literature is also designed to discover areas holding the potential for future research. Research streams are divided into five major categories: demand factors, theory and guidance, enabling technologies, applications, and impacts. Over eighty papers have been identified that relate to these areas. Many more articles exist especially in the area of enabling technologies. However, the focus of our paper is the literature most closely related to continuous audit.
Keywords: Accounting; Dean's Office